circ_0075048 silencing regulates LCP1 to improve IL-1β-induced chondrocyte injury by binding with miR-663b - Pin Zhang; Ru Pei; Quanhu Shen (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteoarthritis (OA) is a common type of degenerative arthropathy. Previous studies have demonstrated that circular RNAs (circRNAs) are involved in the progression of OA. This study aimed to investigate the role and associated mechanism of circ_0075048 in OA. Methods The expression of circ_0075048 was analyzed based on the Gene Expression Omnibus dataset GSE178724. Human chondrocytes were stimulated with IL-1β to establish an in vitro OA model. Bioinformatic analysis was performed to identify target genes of circ_0075048. The expression of circ_0075048, miR-663b, and LCP1 was detected by quantitative reverse transcription-polymerase chain reaction. The cell viability and apoptosis of C28/I2 cells were determined using Cell Counting Kit-8 assay and flow cytometry. Protein expression was detected using western blotting. Results The expression of circ_0075048 was up-regulated in IL-1β-induced chondrocytes. circ_0075048 silencing promoted the viability of and inhibited the apoptosis of and extracellular matrix (ECM) production of chondrocytes. circ_0075048 was found to be a sponge of miR-663b and LCP1 was found to be a target of miR-663b. circ_0075048 silencing increased miR-663b expression but decreased LCP1 expression levels in chondrocytes. An miR-663b inhibitor eliminated the protective effect of a circ_0075048 small interfering RNA (siRNA) on chondrocytes. However, an LCP1 siRNA abolished the effect of the miR-663b inhibitor on chondrocytes. Conclusion circ_0075048 silencing inhibited the apoptosis of and ECM degradation in IL-1β-induced chondrocytes by regulating miR-663b/LCP1 axis.